2015
DOI: 10.1007/s00248-015-0649-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity in Microbial Mats and Sediments from the Atacama Desert

Abstract: The Atacama Desert has extreme environmental conditions that allow the development of unique microbial communities. The present paper reports the bacterial diversity of microbial mats and sediments and its mineralogical components. Some physicochemical conditions of the water surrounding these ecosystems have also been studied trying to determine their influence on the diversity of these communities. In that way, mats and sediments distributed among different hypersaline lakes located in salt flats of the Atac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 78 publications
8
41
2
Order By: Relevance
“…However, given the limited presence of cyanobacterial as well as proteobacterial OTUs in our samples, it is plausible that, in addition to the Halobacteria discussed above, other organisms such as Acetothermia contribute to community CO 2 fixation in Tebenquiche. The scarcity of cyanobacteria in the current study corroborates earlier observations of a low cyanobacterial presence in mats and evaporites from the Salar de Atacama (Farías et al, 2013, 2014; Rasuk et al, 2014, 2016). However, we cannot rule out that the cyanobacterial community comprises a few species with high abundance, and high metabolic activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, given the limited presence of cyanobacterial as well as proteobacterial OTUs in our samples, it is plausible that, in addition to the Halobacteria discussed above, other organisms such as Acetothermia contribute to community CO 2 fixation in Tebenquiche. The scarcity of cyanobacteria in the current study corroborates earlier observations of a low cyanobacterial presence in mats and evaporites from the Salar de Atacama (Farías et al, 2013, 2014; Rasuk et al, 2014, 2016). However, we cannot rule out that the cyanobacterial community comprises a few species with high abundance, and high metabolic activity.…”
Section: Discussionsupporting
confidence: 92%
“…Several of the HAAL ecosystems have been described (Thiel et al, 2010; Farías et al, 2013; Gomez et al, 2014; Rasuk et al, 2016), but relatively little is known about the microbial diversity of the community in relation to biogeochemistry, especially that of the benthic ecosystems. The current investigation is the first in which the total microbial diversity was evaluated and interpreted in relation to the geochemical and physicochemical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a mean of 266 (SE, 7.5) OTUs for the mat studied here compared to a mean of 256 (SE = 16.2) for the mats studied by Stanish et al (2013). These results are also similar to the studies of hypersaline mats of the Atacama Desert region (Farías et al 2013;Rasuk et al 2016;Fernandez et al 2016). For example, Fernandez et al (2016) reported between 121 Collector's curves or alpha-rarefaction plots for the 16S community (a), and the 18S community (b) in the microbial mat, defined at 97% SSU rDNA sequence identity.…”
Section: Resultssupporting
confidence: 88%
“…2, include Rhodobacter, Rubellimicrobium, and members of the Acetobacteraceae, including Roseococcus. Previous studies have implicated PPB (e.g., the Rhodospirillales) as playing important roles in high-elevation soils and sediments in the Rockies, Andes, and Himalayas (Demergasso et al 2010;King et al 2010a, b;Rasuk et al 2016;Schmidt et al 2011), including some of the highest elevation (>6000 m.a.s.l.) sites on Volcán Llullaillaco in the Atacama Desert (King et al 2010a, b).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, many studies have investigated the Atacama Desert (Desierto de Atacama) located as a plateau in South America along the Pacific coast to the west of the Andes mountains. It is the driest, non-polar and oldest desert on Earth (Farías et al 2014;Rasuk et al 2014Rasuk et al , 2016. Recent findings (Rasuk et al 2016) have indicated that a large proportion of 16S sequences could not be classified at the phylum level, which may indicate a new phylum is present in this Desert.…”
Section: Introductionmentioning
confidence: 99%